Peirce's Triadic Model of Sign on Tempo Digital Newspaper Cover 21st October 2024 Edition - Dwi Khumaeroh Sa'adah; R. Myrna Nur Sakinah (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2025)
Signs can be found anywhere, as exemplified by the cover of the October 21, 2024, edition of the Tempo digital newspaper, which reflects the prevailing political landscape in Indonesia. This research aims to classify the sign elements in the illustration of the Tempo digital newspaper cover and analyze their meanings. The method employed to examine these signs and meanings is qualitatively descriptive, utilizing the Triadic Model of Sign theory established by Peirce. The results of this research indicate that the seven components of the sign present in the cover show the relationship among representamen (qualisign, sinsign, and legisign), object (icon, index, and symbol), and interpretant (rheme, dicisign, and argument), which collectively contribute to the formation of meaning. This research retains significance due to its potential to enhance readers’ understanding of signs and their meanings while raising public awareness of signs that often communicate implicit messages. The research concludes that the signs featured on the cover of Tempo’s digital newspaper, ‘Dwifungsi Pengusaha-Menteri,’ appear to deliver a cautionary message to the audience, prompting them to observe and evaluate the actions of the ministers.